Strategi Guru Kelas Dalam Minat Belajar Peserta Didik Sekolah Dasar - Moh Riski Budi; Adawiyah S Pettalong; Jumri Hi. Tahang Basire; Naima; Mudaimin; Elya (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2026)
This study aims to examine the classroom teacher’s strategies in improving the learning interest of fifth-grade students at SD Al-Khairaat Pusat Palu and to identify the supporting and inhibiting factors in their implementation. This research is a field study using a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The findings indicate that the teacher’s strategies in enhancing students’ learning interest have not been implemented optimally. The teacher has used instructional media in certain subjects and created a conducive learning environment through classroom management and short engaging activities to reduce students’ boredom. However, the use of learning media is not yet applied consistently across all subjects. The main obstacles include limited learning resources and media, difficulties in classroom management, and low student motivation and discipline. This study is limited to one school and one class and does not quantitatively measure the level of improvement in students’ learning interest. Therefore, future research is recommended to use quantitative or mixed methods approaches, involve a broader research setting, and examine additional factors such as parental involvement and the use of technology-based learning media.